TINGKAT STRES DAN KOPING INDIVIDU DENGAN DERAJAT DISMENORE PADA REMAJA PUTRI - Anggraeni, Suci; Monteiro , Angeline Febriyani; Yalestyarini, Eva Agustina; Hidajaturrokhmah, Nur Yeny (Jurnal EDUNursing, 2024)
Stress is one of the causes of primary dysmenorrhea. Mild stress is a stressor that is faced regularly which can last for minutes or hours. The purpose of this study was to determine the relationship between stress levels and individual coping with the degree of dysmenorrhea in female adolescents at SMPN 1 Bandung, Bandung District, Tulungagung Regency. This study used a correlation analysis design with a cross-sectional approach. The population of this study were 177 female students of SMPN 1 Bandung who had experienced dysmenorrhea. The sampling technique in this study used stratified random sampling, the instruments used were questionnaires, and statistical tests used interval regression. The results of each variable obtained respondents who experienced severe stress levels were 64 respondents (36.16%), respondents who had good individual coping were 67 respondents (37.85%), respondents who experienced mild dysmenorrhea were 70 respondents (39.55%). %). The results of the linear regression statistical test obtained a coefficient value of 0.727 and a p-value of 0.000 <0.05, so it can be concluded that there is a relationship between stress levels and individual coping with the degree of dysmenorrhea in female adolescents at SMPN 1 Bandung, Bandung District, Tulungagung Regency. The linear regression coefficient value of 0.727 indicates that the strength of the relationship between these three variables is in the strong category. Stress is one of the causes of dysmenorrhea in female adolescents so that stress level management is needed, controlling stress levels, and providing individual coping education to adolescents. Suggestions that can be given to schools are to pay more attention to the stress levels of female students who experience dysmenorrhea so that dysmenorrhea pain in female students does not increase and can interfere with learning concentration. Keywords: Dysmenorrhea, Individual Coping, Female Adolescents, Stress